ADVENTURE TOURISM IN UZBEKISTAN - Nazarova Malika (TADQIQOTLAR, 2025)
This  research  provides  a  comprehensive  analysis  of  the  development, challenges, and prospects of adventure tourism in Uzbekistan. The study investigates the country’s natural landscapes, government initiatives, and international interest in outdoor and cultural experiences. Data from national tourism agencies, global reports, and stakeholder interviews are utilized to highlight current trends and identify areas for growth.  Findings  indicate  that  Uzbekistan  holds  strong  potential  for  becoming  a leading adventure tourism destination in Central Asia due to its unique geographical diversity  and  cultural  richness.  However,  infrastructure  improvement,  safety regulations,  and  sustainable  tourism  practices  remain  essential  for  sector development.These  findings  contribute  to  the  understanding  of  sustainable development in emerging adventure destinations and provide actionable insights for tourism stakeholders.